Análisis de la planta turística, oferta alimentos en el cantón Salcedo. - Sangucho Tello, Ana Fernanda (2020)
Salcedo, Cotopaxi province, an area with natural resources and varied gastronomy. This research project had as a general objective the tourist plant analysis offering food and drinks updating the information of the establishments in the canton, for this a diagnosis was made, through the analysis and tabulation of the obtained information, and the comparison with data from primary and secondary sources (books, articles, magazines, and files on the subject) of the Ministry of Tourism and GAD Municipal de Salcedo organizations in charge of this area, determining the current state at geographical, social, economic, environmental and tourism field focused on the supply tourist plant offering food and drinks, and as a result it was obtained that Salcedo is economically handles on activities such as agriculture and livestock as a primary source, and as secondary tourism. For the fulfillment of the second objective, field trips were carried out, visiting the establishments owners to fill in technical files where the main information, human talent, types of establishments, infrastructure, signaling, services, modality and additional services were determined, getting that the use of technology for the promotion of its services is scarce due to the lack of knowledge of ICTs use. In addition, it allowed to obtain the final result of 42 establishments classified on; 29 restaurants, 3 bars and discos, 2 coffee shops, 4 food places and 4 catering services. The third objective was concluded with the creation of food and beverage establishments catalog, where relevant information about the equipment, offered services, address, telephone and QR code is disclosed, which will allow to the reader to enter on accurately location of the establishments providing their information. The catalog is the final result of this investigation, thus being an informative tool that will be used as a benefit for the owners.